Symposium 3: Assessing the value of design narratives, patterns and scenarios in scaffolding co-design processes in the domain of technology enhanced learning - Mor, Yishay; Warburton, Steven (Proceedings of the International Conference on Networked Learning, 2014)
In order to promote pedagogically informed use of technology, educators need to develop an active, inquisitive, design-oriented mind-set. Design Patterns have been demonstrated as powerful mediators of theory-praxis conversations yet widespread adoption by the practitioner community remains a challenge (Goodyear et al., 2004). Over several years, the authors and their colleagues have facilitated many workshops in which participants shared experiences, captured these as design narratives, extracting design patterns, and applied them to novel teaching challenges represented as design scenarios. This paper analysis the value of design narratives, patterns and scenarios in scaffolding co-design processes in light of previous work in this area.